Acute Kidney Injury (AKI) in Critically Ill Patients: Diagnosis, Management, and Outcomes (Medical Forum Monthly, 2024)
Objective: The proposed research is intended to assess diagnostic approaches, management and prognoses of AKI in 150 critically ill patients admitted in an ICU.Study Design: A prospective cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of Nephrology, Mercy Teaching Hospital, Peshawar from Jan 2021 to Jan 2022.Methods: A total of 150 patient who were critically ill were recruited in a prospective study. AKI was defined by KDIGO criteria, treatment included maintenance of fluid and electrolyte balance, initiation of RRT and correction of predisposing factors. If patient survival was the end of therapy measure, then similar assessment was done with regards to patient survival rates and kidney recovery. The means were analyzed, and also the standard deviation, as well as p-value, to ascertain the significance in the results shown below.Results: In this study 45% of the 150 patients studied had AKI. The mean of the disease was noted to be 2. 8 mg/dL ± 0. 5 of serum creatinine at diagnosis. Hemodialysis was started in 30 percent of patients with AKI. The overall mortality of the patients on RRT was 55% and the total mortality of the patients was 35%. The variability in creatinine levels was ± 0. 5 and the probability for the differences of survival between the patients receiving RRT and those who did not was < 0. 01 meaning that the differences were statistically significant.Conclusion: AKI in critically ill patients is further related with high mortality predominantly in patients on RRT. It was observed that intervention at an early stage of the disease process and management of patients according to the probable aetiology can enhance the life span and diminish the magnitude of renal dysfunction in the long-term follow-up.